An investigation into linguistic bases of desining an ESP reading syllabus for 3rd year students of English for International Relations at Diplomatic Academy of Vietnam - Nguyễn, Thị Thúy Hằng (University of Languages and International Studies, 2017)
Chapter I, “Literature Review” reviews such the relevant theories as prominent linguistic features of international news on papers, an overview of ESP, approaches to language syllabus, reading, as well as previous studies. Chapter II, “The study” describes and comments on situation analysis, subjects of the study, the instruments for collecting data, the theory of Needs Analysis and the findings of the study resulting from a statistical analysis of the collected data. Chapter III presents some recommendations for “designing an ESP reading syllabus for students at the EIR at DAV”.